A Short Review of Anti-Rust Fungi Peptides: Diversity and Bioassays - Lintz, Julie; Dubrulle, Guillaume; Cawston, Euan; Duplessis, Sébastien; Petre, Benjamin (Frontiers in Agronomy, 2022)
Pucciniales are fungal pathogens of plants that cause devastating rust diseases in agriculture. Chemically-synthesized pesticides help farmers to control rust epidemics, but governing bodies aim at limiting their use over the next decade. Defense peptides with antimicrobial activities may help to innovate a next generation of phytosanitary products for sustainable crop protection. This review comprehensively inventories the proteins or peptides exhibiting a biochemically-demonstrated antifungal activity toward Pucciniales (i.e., anti-rust proteins or peptides; hereafter ‘ARPs’), and also analyses the bioassays used to characterize them. In total, the review scrutinizes sixteen publications, which collectively report 35 ARPs. These studies used either in vitro or in plantabioassays, or a combination of both, to characterize ARPs; mostly by evaluating their ability to inhibit the spore germination process in vitro or to inhibit fungal growth and rust disease development in planta. Also, the manuscript shows that almost no mode of action against rust fungi was elucidated, although some might be inferred from studies performed on other fungi. This short review may serve as a knowledge and methodological basis to inform future studies addressing ARPs.